2024
DOI: 10.1002/agj2.21540
|View full text |Cite
|
Sign up to set email alerts
|

Peanut (Arachis hypogaea L.) response to low‐rate applications of selected herbicides at vegetative and reproductive growth stages

Navjot Singh,
Olumide S. Daramola,
Joseph E. Iboyi
et al.

Abstract: Off‐target drift of herbicides can seriously reduce peanut (Arachis hypogea L.) growth and yield and is of great concern to growers who will need to manage sensitive crops near new herbicide‐tolerant crops. Field experiments were conducted in 2021 and 2022 with 25% labeled rates of dicamba, glufosinate, glyphosate, lactofen, and paraquat to simulate drift on peanut. The objective was to evaluate the effects of low‐rate application of the herbicides on peanut injury and yield reductions and to determine if unma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…According to the observations taken during the systematic conduction of the experiment with good maintenance of the experimental plots, we have concluded that as the branching of groundnut increases, the yield also increases, respectively. However, the extent of increase in yield and branching varies for different treatments and those differences in the yield obtained were given below: The number of branches led to an increase in yield based on different types of treatments in different experiments were reported in findings of Shashidhar VR, et al [3], Gowthami V, et al [4], Nigam SN, et al [5], Ali FM, et al [6], Avinasha BL, et al [7], Nagar R, et al [8], Oppong SD, et al [9], Thilini SPLNK, et al [10], Gawas D, et al [11], Magagula N, et al [12], Sathiya K, et al [13], Mohanty P, et al [14], Ibrahim II, et al [15], Yilmaz M, et al [16], Iddrisu A, et al [17], Singh N, et al [18], El Naim AM, et al [19], Seijo G, et al [20], Maleki SJ, et al [21], Michael CY, et al [22], Sanders TH, et al [23,24], Veeramani P, et al [25].…”
Section: Resultsmentioning
confidence: 99%
“…According to the observations taken during the systematic conduction of the experiment with good maintenance of the experimental plots, we have concluded that as the branching of groundnut increases, the yield also increases, respectively. However, the extent of increase in yield and branching varies for different treatments and those differences in the yield obtained were given below: The number of branches led to an increase in yield based on different types of treatments in different experiments were reported in findings of Shashidhar VR, et al [3], Gowthami V, et al [4], Nigam SN, et al [5], Ali FM, et al [6], Avinasha BL, et al [7], Nagar R, et al [8], Oppong SD, et al [9], Thilini SPLNK, et al [10], Gawas D, et al [11], Magagula N, et al [12], Sathiya K, et al [13], Mohanty P, et al [14], Ibrahim II, et al [15], Yilmaz M, et al [16], Iddrisu A, et al [17], Singh N, et al [18], El Naim AM, et al [19], Seijo G, et al [20], Maleki SJ, et al [21], Michael CY, et al [22], Sanders TH, et al [23,24], Veeramani P, et al [25].…”
Section: Resultsmentioning
confidence: 99%